Development of Parameters of Road Conditions based on Road User/Citizen Satisfaction - Eliza Rosmaya Puri (IPTEK Journal of Proceedings Series, 2017)
The study focused on the parameters of road conditions in a city road network in Indonesia. It also assessed the satisfaction level of road users/citizens within two streets in Cimahi city, Indonesia. In achieving this objective, literature reviews and opinions of 30 road users/citizens for each street were sampled using two key questions. The data collected were analysed using descriptive statistics. The analysis revealed that the satisfaction level of road users/citizens is 2.53 and 1.67 respectively, which conforms to the result of a road condition survey in the two streets. The reasons for satisfaction based on the road users’/citizens’ perspective were the good physical conditions of the road/drainage. In contrast, the reasons for dissatisfaction were unstable physical road conditions related to city maintenance activities, late/deferred maintenance and inappropriate maintenance. Road users/citizens found such maintenance activities contributed to four specific physical conditions of roads/drainage in the city: a small volume of pavement distress in scattered areas, moving road deterioration, seasonal floods and water ponds and the rapid decay of newly paved roads. The physical conditions also conform to the result of a road conditions survey for the two streets. Besides this, other physical conditions of roads/drainage contributing to unstable road conditions found by an expert are unconnected road networks due to natural disasters. The study recommended the five physical conditions of roads/drainage as a new set of parameters for road conditions for the city network in Indonesia. The new set of road condition parameters can be applied to benchmark and compare a city road condition for each parameter and also display the derived overall road performance.